DIGITAL POLITICS AND THE RISE OF "CYBER TROOPS": A STUDY OF SOCIAL MEDIA MANIPULATION AND ITS IMPACT ON INDONESIAN DEMOCRACY - Costa, João; Silva, Maria; Santos, Pedro (Cognitionis Civitatis et Politicae, 2026)
The proliferation of social media in Indonesia has introduced new dynamics in the political landscape. The rise of "cyber troops" groups or individuals paid to manipulate public opinion online has become a significant challenge to democratic processes. Social media platforms, once considered powerful tools for political engagement, are now being used to spread misinformation, propaganda, and polarizing content, undermining democratic integrity. This study aims to explore the role of social media manipulation through cyber troops and its impact on Indonesian democracy. Specifically, it investigates the techniques used by cyber troops to sway public opinion and the consequences for democratic processes, such as elections and public policy debates. A qualitative research approach was employed, utilizing content analysis of social media campaigns, interviews with political analysts, and case studies of recent political events in Indonesia. The study also examines the legal and ethical frameworks surrounding digital political manipulation. The research reveals that cyber troops significantly influence voter behavior and public discourse in Indonesia, creating a distorted political narrative. These activities have led to increased polarization and undermined public trust in democratic institutions. The study concludes that while social media has enhanced political engagement, it has also facilitated the manipulation of public opinion, posing risks to the democratic process in Indonesia. Effective regulation and media literacy initiatives are essential to mitigate the influence of cyber troops.